Overexpression of BUB1B contributes to progression of prostate cancer and predicts poor outcome in patients with prostate cancer - Fu, Xin (Onco Targets Ther, 2016)
BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) is a member of the spindle assembly checkpoint protein family, which has been proven to be associated with many kinds of cancers. The aim of this study was to investigate whether BUB1B was correlated with progression and prognosis in patients with prostate cancer (PCa) and how BUB1B regulated the proliferation, migration, and invasion of PCa cell lines. Compared to benign prostate cells and tissues, both messenger RNA and protein expressions of BUB1B were statistically increased in PCa cell lines and tumor tissues. In vitro studies revealed that BUB1B overexpression enhanced the proliferation, migration, and invasion ability of PCa cell lines, whereas depletion of BUB1B did not affect the cell functions. Microarray analysis showed the positive staining of BUB1B was upregulated in the higher Gleason score group, which also correlated with advanced clinicopathological stage, higher serum prostate-specific antigen, metastasis, overall survival, and prostate-specific antigen failure. Furthermore, the survival analysis indicated that high expression of BUB1B was an independent predictor for shorter biochemical recurrence-free survival, which had no effect on overall survival. BUB1B plays an important role in tumor growth and progression, which can lead to its use as a potential biomarker for the diagnosis and prognosis of PCa.